1991
DOI: 10.1021/bi00242a010
|View full text |Cite
|
Sign up to set email alerts
|

Removal of salt from a salt-induced protein crystal without cross-linking. Preliminary examination of "desalted" crystals of phosphoglucomutase by x-ray crystallography at low temperature

Abstract: A model procedure for removing salt from relatively fragile salt-induced protein crystals is proposed. The procedure is based on physical principles and is validated by using millimeter-size crystals of rabbit muscle phosphoglucomutase grown from a 2.1 M solution of ammonium sulfate. Three types of operations are included in the procedure: initial transfer to salt solutions of reduced concentration; transfer to the organic-rich phase of an equilibrium biphasic mixture obtained with aqueous solutions of polyoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…"/,~ was observed. (Teng, 1990;Ray et al, 1991). Many have noted an increase in the crystal lifetime and an improvement in the diffraction resolution of crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"/,~ was observed. (Teng, 1990;Ray et al, 1991). Many have noted an increase in the crystal lifetime and an improvement in the diffraction resolution of crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Another critical factor in the experiments was the 24-step transfer of crystals into the cryoprotective mixtures. Most recently, Ray et al (1991) demonstrated the importance of very gradual changes in the concentrations of additives to crystals to prevent internal osmotic shocks which caused irreversible damage. Because PEG was introduced by gradual transfer techniques, the solvent content was lowered by 6% without crystal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of the exchange of mother liquor sometimes leads to crystal cracking and/or significant loss of the X-ray scattering power of the crystals. This could in some cases be related to crystal crushing by osmotic pressure, especially when high-ionic-strength precipitant is exchanged for polyglycols (Ray, Puvathingal, Bolin, Minor, Liu & Muchmore, 1991). More often, however, crystal cracking is due to changes in the unit-cell dimensions that result from conformational adjustments induced by ligand binding to the protein molecules and subsequent changes in intermolecular contacts.…”
mentioning
confidence: 99%
“…In some applications up to 40 exchanges of mother liquor were used (Ray et al 1991). It should be mentioned, however, that if the ligand binding is virtually irreversible then even very low concentrations of the ligand may lead to a large gradient of the protein-ligand complex in the crystals.…”
mentioning
confidence: 99%